K to 12 transition in action: Threading the opportunities and challenges on the implementation of senior high school sports track in Southern Philippines - Poblador, Steffany Anne C; Tagare, Ruben Lagunero (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
This study aimed to determine the opportunities and challenges in the implementation of the Senior High School Sports Track program during the transition years of the Philippine K to 12. To accomplish the study's objectives, a Qualitative – Phenomenology Research Design was employed to draw more explicit portraits of the different opportunities and challenges confronting the selected Senior High School Teachers in the Province of Cotabato, Philippines. A series of interviews were used as the primary strategy for obtaining the necessary data. Validation and triangulation of the findings indicated six (6) key themes expressed by research participants. These include the following: Encourage other schools to offer a sports track program; develop and enhance teacher development programs and initiatives; establish admission and retention policy for senior high school sports track students; recommend curriculum mapping to align competencies with learners; hire more skilled teachers; allocate funding for facility improvements and equipment purchase. The data were then used to develop practical recommendations for improving the Philippines' Senior High Sports Track Program.